Strategi Komunikasi Bisnis Pengusaha Usaha Mikro Kecil dan Menengah di Kota Mojokerto saat Pandemi Covid-19 - Nuriyahsari, Nisa Maharani Putri Pratama; Turmudzi, Imam (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
During the Covid-19 pandemic, human life was hampered, one of which economic sector, for example the Micro, Small and Medium Enterprises (UMKM) sector in the footwear industry in Mojokerto City, namely UD Perdana and Athyyah. Entrepreneurs have difficulty getting raw materials, market share has decreased, public trust has decreased, the loss business partners has resulted drastic decrease in turnover and even not operating for several months. Therefore, need business communication strategy to restore conditions normal. The focus this research: 1)What are the efforts of UMKM to build communication their business partners in maintaining their existence during Covid-19 pandemic in Mojokerto City? 2)What is business communication strategy UMKM in maintaining their existence during Covid-19 pandemic in Mojokerto City? 3)What are the factors that hinder UMKM maintaining their existence during Covid-19 pandemic in Mojokerto City?. Research method used descriptive qualitativ. Data collection use observation, interviews, documentation. Data analysis uses Miles and Huberman model. Validity of data using triangulation sources and techniques. The results of research: 1)The efforts UMKM to build communication their business partners through business communication, namely changes knowledge, attention, behavior. 2)The business communication strategy UMKM is through marketing mix strategy. UD Athyyah's product strategy: brand innovation, new types. UD Perdana: brand innovation, new models and types. Price strategy:cheaper if take directly on location. UD Athyyah's promotion strategy: digital advertising, UD Perdana: using personal selling. Place strategy in the form of flexibility in the distribution,direct collection of goods. 3)Inhibiting factors market share, government policies, social change, technological developments.